Autogenic Drainage "The flow and breathing level modulation concept" - Chevaillier, Jean (Trivium fisoteràpia, 2016)
This work does not provide "recipes" or standardized solutions for the treatment of patients affected hypersecretion. The reader will find the book necessary ingredients to adapt to drain bronchial disease and the patient's condition, their needs and possibilities. Find relevant information ontology, anatomy, physiology and pulmonary ventilatory mechanics in order to facilitate understanding of the mechanisms involved in bronchial drainage techniques. It also delves into measurements of lung function and its implications. Explains the problems with obstruction and pulmonary physiotherapy assessment, as well as the bases of the bronchial drainage techniques. Not to mention the care of the upper airways. Acquire special mention specific principles of autogenic drainage, showing through performance curves partial expiratory flow-volume, the ability to modulate the flow and volume in the bronchial tree and selectively localize functional bronchial generations drain. Series of tips to standardize ventilation during inspiratory phase as well as the importance of correcting the shape of the rib cage. Explains the use of autogenic drainage in patients collaborators and collaborators, with a section dedicated to autogenic drainage in infants. The last chapters are devoted to explaining the specific physiology of cough with practical implications, special attention is given to inhalation therapy and finally being mentioned techniques as accessory respiratory reeducation and functional analysis, the importance of exercise and positioning, flexible gymnastics, relaxation, the use of oxygen and the rehabilitation effort through sport.